Field Nitrogen Losses Induced by Application Timing of Digestate from Dairy Manure Biogas Production. Issue 6 (1st November 2016) - Schwager, Emily A.; VanderZaag, Andrew C.; Wagner‐Riddle, Claudia; Crolla, Anna; Kinsley, Chris; Gregorich, Ed
Abstract : Anaerobic digestion of dairy manure has environmental benefits, but the impact of effluent (i.e., digestate [DG]) application on environmental nitrogen (N) losses from soils has not been well quantified. Our objective was to evaluate how field application of DG affected nitrous oxide (N2 O) emissions and nitrate (NO3 ) leaching compared with raw dairy manure (RM) in spring versus fall applications. We measured N losses year‐round for 2.5 yr in silage corn on tile‐drained clay soil in Alfred, Ontario, Canada. Treatments were: digestate applied in spring (DS) and fall (DF), raw dairy manure applied in spring (RS) and fall (RF), urea applied in spring, and a control. Overall, the source of N had no effect on annual N2 O emissions (overall average DG and RM, 4.9 kg N2 O–N ha −1 yr −1 ), but more NO3 leached from DS than RS treatments (8.8 and 4.8 kg NO3 –N ha −1 yr −1 on average, respectively). Estimated indirect N2 O emissions from leached NO3 –N were small (<0.2 kg N2 O–N ha −1 yr −1 ). Timing of application did not affect annual N2 O emissions but did shift emissions to the non‐growing season for fall applications (65% on average) and to the growing season for spring applications (60% on average). Overall environmental N losses (N2 O–N + NO3 –N) from DG were similar to RM when applied at the same time. For the conditions of our study, downstream emissions from anaerobic digestion (i.e., emissions induced by applied digestate) do not present an adverse trade‐off to the environmental benefits incurred during the biogas production phase. Core Ideas: Biodigestion has environmental benefits, but N losses from soils are uncertain. Nitrous oxide emissions and NO3 leaching were evaluated. Digested and raw manure had similar annual N losses. Application in spring had lower annual NO3 losses than fall application. Soil emissions were not a trade‐off to environmental benefits of biogas production.